In-vitro haemocompatibility of dextran-protein submicron particles - Chiraphat Kloypan; Nittiya Suwannasom; Saranya Chaiwaree; Ausanai Prapan; Kathrin Smuda; Nuttakorn Baisaeng; Axel Pruß; Radostina Georgieva; Hans Bäumler (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Blood compatibility is a key requirement to fulfil for intravenous administration of drug and oxygen carrier system. Recently, we published the fabrication of oxidised-dextran (Odex)-crosslinked protein particles by one-pot formulation. In the current study we investigate the haemocompatibility of these Odex - particles including albumin particles (Odex-APs) and haemoglobin particles (Odex-HbMPs). Odex-APs and Odex-HbMPs have a submicron size ranged 800–1000 nm with peanut-like shape and a negative surface charge. In vitro haemocompatibility assays included haemolysis test, indirect phagocytosis test and platelet activation test in human blood. Odex-APs and Odex-HbMPs did not provoke any undesirable effects on the blood cells. Firstly, the ratio of haemolysis after contacted with Odex-crosslinked protein particles were less than 5% and therefore the particles may be considered non-haemolytic. Secondly, the incubation of leukocyte with Odex-APs/HbMPs did not influence the phagocytosis of leukocyte. We conclude that our particles are not recognized by monocytes or granulocytes. Finally, exposure of Odex-APs/HbMPs to platelets did not cause an activation of platelets. Additionally, Odex-HbMP/AP did not enhance or attenuate agonist-induced platelet activation. We conclude that Odex-crosslinked protein particles exhibit a very good haemocompatibility and represent highly promising carriers for drugs or oxygen.